Minimally invasive distal pancreatectomy: Laparoscopic versus robotic approach—A cohort study. Issue 4 (4th July 2022) - Lai, Hon‐Fan; Shyr, Yi‐Ming; Shyr, Bor‐Shiuan; Chen, Shih‐Chin; Wang, Shin‐E; Shyr, Bor‐Uei
Abstract: Background and Aims: There is no consensus on the superiority of robotic distal pancreatectomy (RDP) over laparoscopic distal pancreatectomy (LDP). Methods: Data of patients undergoing RDP and LDP were prospectively collected and compared. Results: There were 65 RDP and 112 LDP. RDP took a shorter operation time than LDP. Overall, DP with splenectomy took a longer operation time than that with spleen preservation. This difference was only significant in LDP group. In both RDP and LDP groups, splenectomy was associated with increased blood loss, as compared with spleen preservation. No significant differences were observed in surgical morbidity between RDP and LDP. The hospital cost in RDP was almost double that of LDP, with a median of 13, 404 versus 7765 USD. Conclusion: LDP is comparable to RDP in regard to surgical outcomes. LDP with spleen preservation is highly recommended whenever possible and feasible for benign or low malignant lesions in terms of lower costs and less blood loss.